Implicit Mentalizing in Patients With Schizophrenia: A Systematic Review and Meta-Analysis - Csulak, Timea; Hajnal, András; Kiss, Szabolcs; Dembrovszky, Fanni; Varjú-Solymár, Margit; Sipos, Zoltán; Kovács, Márton Aron; Herold, Márton; Varga, Eszter; Hegyi, Péter; Tényi, Tamás; Herold, Róbert (Frontiers in Psychology, 2022)
Introduction Mentalizing is a key aspect of social cognition. Several researchers assume that mentalization has two systems, an explicit one (conscious, relatively slow, flexible, verbal, inferential) and an implicit one (unconscious, automatic, fast, non-verbal, intuitive). In schizophrenia, several studies have confirmed the deficit of explicit mentalizing, but little data are available on non-explicit mentalizing. However, increasing research activity can be detected recently in implicit mentalizing. The aim of this systematic review and meta-analysis is to summarize the existing results of implicit mentalizing in schizophrenia Methods A systematic search was performed in four major databases: MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science. Eleven publications were selected. Five studies were found to be eligible for quantitative synthesis, and 9 studies were included in qualitative synthesis. Results The meta-analysis revealed significantly lower accuracy, slower reaction time during implicit mentalizing in patients with schizophrenia. The systematic review found different brain activation pattern, further alterations in visual scanning, cue fixation, face looking time, and difficulties in perspective taking. Discussion Overall, in addition to the deficit of explicit mentalization, implicit mentalization performance is also affected in schizophrenia, if not to the same extent. It seems likely that some elements of implicit mentalization might be relatively unaffected (e.g., detection of intentionality), but the effectiveness is limited by certain neurocognitive deficits. These alterations in implicit mentalizing can also have potential therapeutic consequences. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier: CRD42021231312.